Structural and chemical changes from CO2 exposure to self-healing polymer cement composites for geothermal wellbores. (January 2021) - Elbakhshwan, Mohamed S.; Gill, Simerjeet K.; Rod, Kenton A.; Bingham, Emma B.; McKinney, Adriana L.; Huerta, Nicolas; Lopano, Christina L.; Kutchko, Barbara G.; Chen-Wiegart, Yu-chen Karen; Zhao, Chonghang; Williams, Garth; Thieme, Juergen; et al.
Highlights: Synchrotron methods provide powerful approach to understand carbonation of polymer cements. Chemical alteration of the polymer-cement follows the rim carbonation mechanism. Self-healing cements maintain compressive strength for EGS applications after CO2 exposure. Abstract: Wellbore cement is subjected to a number of mechanical, thermal and chemical stress regimes over its lifetime. Therefore, next-generation wellbore cement formulations need to be evaluated in conditions relevant to these environments. In this work, we investigate the mechanism of the alteration of a novel self-healing polymer-cement composite after exposure to a CO2 -rich environment by using synchrotron-based X-ray Fluorescence (XRF), X-ray absorption near edge structure (XANES), and scanning electron microscopy coupled with energy dispersive spectroscopy. Results showed that a chemical alteration of the polymer-cement follows the rim carbonation mechanism, similar to conventional cement, although carbonation takes place to a lesser extent in polymer-cements despite the higher porosity. Along with detailed mechanistic insights on carbonation in polymer-cement composite, the performance of these in CO2 -rich environment is further studied using standard compressive strength analysis.